Activation of apoplastic sugar at the transition stage may be essential for axillary bud outgrowth in the grasses - Kebrom, Tesfamichael H.; Doust, Andrew N. (Frontiers in Plant Science, 2022)
Axillary buds are formed from meristems in leaf axils. The buds enter a transition stage before growing into branches, or transition into dormancy if internal and environmental factors limit sucrose supply to the buds. A fundamental question is why sucrose can be limiting at the transition stage for bud outgrowth, whereas new buds continue to be formed. Sucrose is transported to sink tissues through symplastic or apoplastic pathways and a shift from symplastic to apoplastic pathway is common during seed and fruit development. In addition, symplastic connected tissues are stronger sinks than symplastically isolated tissues that rely on sugars effluxed to the apoplast. Recent studies in the grasses indicate activation of apoplastic sugar in buds that transition to outgrowth but not to dormancy, although the mode of sugar transport during bud formation is still unclear. Since the apoplastic pathway in sorghum buds was specifically activated during bud outgrowth, we posit that sugar for axillary bud formation is most likely supplied through the symplastic pathway. This suggests a key developmental change at the transition stage, which alters the sugar transport pathway of newly-formed buds from symplastic to apoplastic, making the buds a less strong sink for sugars. We suggest therefore that bud outgrowth that relies on overflow of excess sucrose to the apoplast will be more sensitive to internal and environmental factors that enhance the growth of sink tissues and sucrose demand in the parent shoot; whereas bud formation that relies on symplastic sucrose will be less affected by these factors.